Quang Quick Breakfazz/ Sharmila Salleh… [et.al.] - Salleh, Sharmila; Mostapha, Melissa Amillia; Mohd Zaidi, Nurul Syuhada; Fatimah, Noorjannah; Isah, Lamban (2008)
The name of our business is Quang-Quick Breakfazz”. The word “Quang-Quick” derived from the Sarawak dialect that is ‘kuang-kuit’ which means commute. Basically it refers to the way we operate our business by selling the product from a place to other places. Meaning to say that, we stop at one place for a certain time and sell our product and go to another place. The word “Breakfazz" originally came from the word breakfast. It is because we only start our operation during breakfast from 7.00 am until 11 .am